Annex 2: An Accolade to Late Gopal Singh Nepali - Editor, The (Himalayan Journal of Sociology and Anthropology, 2008)
The editors of the current issue would like to extend their heartiest thanks to Mr. Sanjeev Nepali and Ms. Sangeeta Nepali, the Children of Prof. G.S. Nepali for providing important materials for preparing this accolade. DOI: http://dx.doi.org/10.3126/hjsa.v3i0.1504 <!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –>Himalayan Journal of Sociology and Anthropology Vol.III, Sept. 2008 p.174-176